2020
DOI: 10.1097/md.0000000000023713
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary edema following shoulder arthroscopy under general anesthesia with nerve block

Abstract: Shoulder arthroscopy requires a large of irrigation for a better surgical view, leading circulatory overload. This study was performed to prove whether pulmonary edema will be lead by a large of irrigation. General anesthesia with interscalene block was induced before operation. The primary outcome was ultrasound evaluation of B lines from the time before nerve block to the time 10 hours after operation. The secondary outcomes included oxygenation index, arterial partial pressure of carbon dioxide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…NB from ultrasound is an important diagnostic indicator of pulmonary edema, which were examined by Naviu color ultrasonic diagnostic system with low-frequency linear array probe (frequency 3.5–5.5 MHz), and 28 intercostal space scanning methods were used to measure NB of bilateral parasternal line, central clavicular line, anterior axillary line, central axillary line and posterior axillary line according to Picano Eugenio. [ 6 , 7 ] The secondary outcomes included the following information of the patient: sex, age, BMI, American Society of Anesthesiologists grade, hypertension, preoperative and postoperative hemoglobin concentration, type of surgery, duration of surgery, irrigation amount, volume of fluid in and out at intraoperative, blood loss, urine volume, dosage of opioids and muscle relaxants and the incidence of postoperative hypoxemia. Postoperative hypoxemia was defined as the lowest PaO 2 /FiO 2 in arterial blood gas ≤300 after oxygen inhalation through the nasal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NB from ultrasound is an important diagnostic indicator of pulmonary edema, which were examined by Naviu color ultrasonic diagnostic system with low-frequency linear array probe (frequency 3.5–5.5 MHz), and 28 intercostal space scanning methods were used to measure NB of bilateral parasternal line, central clavicular line, anterior axillary line, central axillary line and posterior axillary line according to Picano Eugenio. [ 6 , 7 ] The secondary outcomes included the following information of the patient: sex, age, BMI, American Society of Anesthesiologists grade, hypertension, preoperative and postoperative hemoglobin concentration, type of surgery, duration of surgery, irrigation amount, volume of fluid in and out at intraoperative, blood loss, urine volume, dosage of opioids and muscle relaxants and the incidence of postoperative hypoxemia. Postoperative hypoxemia was defined as the lowest PaO 2 /FiO 2 in arterial blood gas ≤300 after oxygen inhalation through the nasal.…”
Section: Methodsmentioning
confidence: 99%
“…[ 6 ] The number of B-lines (NB) from ultrasound also plays an important role in evaluating the severity of pulmonary edema. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al . found a 12.9% incidence of moderate‐to‐severe pulmonary edema through 93 patients who had arthroscopic surgery 11 . Sari et al .…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Zhang et al found a 12.9% incidence of moderate-to-severe pulmonary edema through 93 patients who had arthroscopic surgery. 11 Sari et al found the incidence of hypothermia after postoperative 2 h was 100% and the hypothermia could lead to increased risk of cardiovascular disease. 12 Therefore, the occurrence of severe post-arthroscopic complications requires consideration on the impact on other organ systems and more effective evaluation factors.…”
Section: Introductionmentioning
confidence: 99%